Peran Ukuran Perusahaan dalam Memoderasi Pengaruh Book-Tax Differences terhadap Pertumbuhan Laba - Riza Praditha; Nur Fatwa Basar; Nurlaila Hasmi; Henni Mande (Al-Buhuts, 2022)
This study aims to analyze the effect of book-tax differences on the profit growth of manufacturing companies both in terms of permanent differences and temporary differences. In addition, this study also analyzes the role of firm size in moderating the effect of book-tax differences on earnings growth. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. By using the purposive sampling method, obtained a sample of 59 manufacturing companies with an observation period of 3 (three) years. The results showed that Book-tax Differences had a positive and significant effect on profit growth, both permanent differences, and temporary differences. Thus, it can be concluded that the greater the book-tax differences, the higher the profit growth. Furthermore, in testing the role of firm size as a moderator, it is shown that firm size is only proven to be able to moderate the relationship between permanent differences and profit growth. Meanwhile, the relationship between temporary differences was not proven to be moderated by firm size.